DYSTOCIA DUE TO FOETAL HYDROCEPHALUS IN A BLACK BENGAL DOE - JANA, D; JANA, M (The Indian Journal of Animal Reproduction, 2010)
A rare case of caprine foetal dystocia due to congenital hydrocephalus monster in a black Bengal doe and its successfu! delivery per vaginum has been reported.